Cybernetic revolutionaries : technology and politics in Allende's Chile - Medina, Eden, 1976- (Cambridge, Mass. : MIT Press, 2011)
Technological and political visions -- Cybernetics and socialism -- cybernetics in the battle for production -- Designing a network -- Constructing the liberty machine -- The October strike -- Cybersyn goes public -- Conclusion : technology, politics, history.